2006
DOI: 10.1016/j.applanim.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ‘maximum price paid’ as an index of motivational strength for farmed silver foxes (Vulpes vulpes)

Abstract: To measure farmed foxes' motivations for full, naturalistic social contact, we constructed an apparatus where they could perform an operant to access stimuli, but then leave freely and thence determine their own bout lengths. Motivational measures based on demand curves can be invalid in such set-ups, and we therefore sought to validate the measure 'maximum price paid'. This was achieved by measuring six silver fox males' maximum operant responding for access or proximity to three resources differing in biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…This suggested that if food is offered ad libitum, foxes might have periods of gorging and of relative fast, a factor potentially adding great day-to-day variability to measures of motivation. In contrast, when we offered food in more limited quantities, the foxes' value of food was closer to our predictions and day-to-day food-use was also more consistent (Hovland et al, 2006). If silver foxes are sensitive to the amount of food provided and this leads to periods where subjects stop eating for more than the 'cut off' period (e.g.…”
Section: Introductioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This suggested that if food is offered ad libitum, foxes might have periods of gorging and of relative fast, a factor potentially adding great day-to-day variability to measures of motivation. In contrast, when we offered food in more limited quantities, the foxes' value of food was closer to our predictions and day-to-day food-use was also more consistent (Hovland et al, 2006). If silver foxes are sensitive to the amount of food provided and this leads to periods where subjects stop eating for more than the 'cut off' period (e.g.…”
Section: Introductioncontrasting
confidence: 49%
“…To examine farmed foxes motivational strength our research group developed an operant apparatus where foxes could work (by pulling a loop) for access to various resources (Hovland, 2005). Our main measure of motivation was the maximum price paid, which was the highest number of pulls foxes were willing to pay before giving up access for 24 h. Although this apparatus ultimately worked well (Hovland et al, 2006), much pilot work was needed to refine the methodology. Our refinement and validation of the apparatus is described elsewhere (Hovland, 2005;Hovland et al, 2006), but here we examine how the presentation of the useful yardstick 'food' could affect how it is used by foxes and perhaps even valued.…”
Section: Introductionmentioning
confidence: 99%
“…Warburton & Mason (2003) similarly found that mink, Mustela vison, worked for access to limited social contact with neighbours, despite being naturally a solitary and territorial species. Hovland et al (2006) in their study of foxes, Vulpes vulpes, found that males would work hard for access to both male and female conspecifics; however, whereas female stimulus animals attracted affiliative responses such as tail wagging, male stimulus animals attracted threat displays. Both these studies suggest that some stimuli are not positive or enriching additions to the standard cage, even if access for them is worked for.…”
Section: Limited Social Contactmentioning
confidence: 99%
“…Maximum price paid (MPP), used to assess motivational strength, is obtained by imposing a series of costs on access to a resource and recording the maximum cost an animal is willing to pay (Hovland et al, 2006;Kirkden et al, 2003). Because individual differences in MPP for a given resource may also reflect non-motivational factors (e.g.…”
Section: Assessment Of Motivation For Enrichmentmentioning
confidence: 99%